2020
DOI: 10.1002/jpln.202000200
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil organic carbon fractions in response to wheat straw incorporation in a subtropical paddy field in China

Abstract: Background: Optimal wheat straw management in paddy fields is important for evaluating soil organic carbon (SOC) dynamics and sustaining soil quality. Aims: We investigated the effects of wheat straw incorporation in paddy soil on the total SOC content, soil labile organic C fractions [water soluble organic C (WSOC), hot‐water soluble organic C (HWSOC), easily oxidizable C (EOC), microbial biomass C (MBC), particulate organic C (POC), and light fraction organic C (LFOC)], and C pool management index (CPMI). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
6
12
0
Order By: Relevance
“…In this study, the rice grain yield and yield components were highest in the HSNPK treatment and lowest in the control. Similar outcomes have been found in other studies (W. Dai, Gao, et al., 2021; Xia et al., 2014; P. Zhang et al., 2015). In addition, we observed that rice grain yield was positively correlated with SOC and TN at a depth of 0–30 cm; these results verified that SOC and TN are pivotal parameters for crop growth (N. Liu et al., 2021; P. Zhang et al., 2015).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, the rice grain yield and yield components were highest in the HSNPK treatment and lowest in the control. Similar outcomes have been found in other studies (W. Dai, Gao, et al., 2021; Xia et al., 2014; P. Zhang et al., 2015). In addition, we observed that rice grain yield was positively correlated with SOC and TN at a depth of 0–30 cm; these results verified that SOC and TN are pivotal parameters for crop growth (N. Liu et al., 2021; P. Zhang et al., 2015).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the rice grain yield and yield components were highest in the HSNPK treatment and lowest in the control. Similar outcomes have been found in other studies (W. Dai, Gao, et al, 2021;Xia et al, 2014;P. Zhang et al, 2015).…”
Section: Relationships Between Rice Grain Yield Bulk Soc and Tnsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, 90 kg N ha −1 was top-dressed in the tillering and panicle initiation stages. Detailed information on agronomic management has been previously described [18].…”
Section: Study Site and Experimental Designmentioning
confidence: 99%